Assessing and minimizing the risk of percutaneous coronary intervention in patients with chronic kidney disease. (2nd November 2018) - Guedeney, Paul; Sorrentino, Sabato; Vogel, Birgit; Baber, Usman; Claessen, Bimmer E.; Mehran, Roxana
ABSTRACT: Introduction : Chronic kidney disease (CKD) is commonly present in patients undergoing percutaneous coronary intervention (PCI). These patients frequently present with more complex coronary artery disease (CAD) and higher risk of peri-procedural and post-procedural adverse events, including bleeding, thrombotic events, and contrast-induced acute kidney injury (CI-AKI). This article contains updated knowledge and management of patients with CKD undergoing PCI. Areas covered : In this article, the pathophysiological mechanisms behind the association of CKD, complex CAD lesions, and complications of PCI are reviewed and the different risk scores available to assess the occurrence of CI-AKI are detailed. Furthermore, various strategies developed to prevent or reduce the impact of complications of PCI are described. Expert commentary : Patients with CKD have remained a challenge in the field of PCI. Several strategies have been evaluated in the last 20 years, with uneven results. Intravascular expansion therapy remains the cornerstone of CI-AKI prevention although recent studies have emphasized the benefit of guided hydration rather than a one-size-fits-all model. N-acetylcysteine and sodium bicarbonate have recently been challenged while pretreatment with high-dose statins may be of interest. Finally, recent studies based on intravascular ultrasound and minimal-to-no-use of contrast media have yielded promising results.